Rosacea patients seeking advice: Qualitative analysis of patients' posts on a rosacea support forum. (3rd March 2016) - Alinia, Hossein; Moradi Tuchayi, Sara; Farhangian, Michael E.; Huang, Karen E.; Taylor, Sarah L.; Kuo, Sandy; Richardson, Irma; Feldman, Steven R.
Abstract: Background : Social media have become outlets for patients to voice opinions and ask questions. Since suffering from rosacea is an isolating experience and the disease is poorly understood, patients use social media to expand their knowledge about the condition. Objective : To understand rosacea patients' online health information seeking habits to obtain a better insight of their educational needs. Methods : Ten percent of posts in online rosacea forum composed of 3350 members and 27 051 posts, discussing patient viewpoints and concern, selected by stratified random sampling. Three hundred and nine queries were directly categorized to patients "seeking advice" by two investigators and qualitatively analyzed. Results : Patients primarily sought advice about treatments ( n  = 155, 50.1%), triggers ( n  = 53, 17.1%), diet ( n  = 48, 15.5%), skin care ( n  = 37, 11.9%) and special presentations of the disease ( n  = 22, 7.1%). Questions frequently pertained to adverse effects, efficacy and target of therapy (78, 49, 30 posts, respectively). Conclusion : Proactively providing reliable resources and comprehensive explanations on treatments, triggers, diet and skin care could be helpful in reducing patients' confusion about rosacea and enhancing rosacea patient–physician relationships.